Strengthening the Capacity of Da'wah Activists in Indonesia's Global Era Through the Integration of Collaboration, Competence, and Digital Technology - Irfan Safrudin; Sitta Resmiyanti Muslimah; Malki Ahmad Nasir; Muhammad Fadhli Muttaqien (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
This research aims to explore the importance of strengthening collaboration among da’wah activists in facing the challenges of globalization. Globalization has brought significant changes in various aspects of life, including in the context of Islamic da’wah. Da’wah activists face the challenge of adapting to global dynamics, expanding intellectual capacity, and using technology effectively. This research uses a qualitative literature review to examine relevant sources and identify ways to strengthen collaboration among da’wah activists. The research results show that strategic collaboration, openness to technological developments, and professionalism in preaching are the keys to success in the global era. Strong collaboration enables Islamic da’wah to address global challenges more effectively and to spread Islamic moral and social values in a multicultural context.